OPTIMASI FORMULA FAST DISINTEGRATING TABLET EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) DENGAN KOMBINASI BAHAN PENGIKAT POLIVINILPIROLIDON DAN PENGHANCURSODIUM STARCH GLYCOLATE - Setiyadi, Gunawan; Ihsani, Salsabila (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Guava leaves (Psidium guajava L.) can be used as an antidiarrheal with the presence of tannin compounds in them. One way to obtain the benefits of guava leaves is to develop them in practical and easy-to-use preparations such as Fast Disintegrating Tablets (FDT) which are very useful for pediatric and geriatric patients who have difficulty swallowing whole tablets. In addition, FDT has a faster onset of action than regular tablets. This study aims to determine the effect of the combination of Sodium Starch Glycolate (SSG) as a disintegrant and polyvinylpyrrolidone (PVP) as a binder and the optimum concentration of the combination of both that provide good physical properties of guava leaf FDT. This study was conducted using a simplex lattice experimental design. The components of the guava leaf FDT formula that were optimized were PVP and SSG, while the response used for formula optimization was the physical properties of the tablet, namely weight uniformity, hardness, fragility, and tablet disintegration time. In this study, the manufacture of guava leaf FDT was carried out using the wet granulation method. The results showed that the optimum formula was obtained at a ratio of PVP 2.947% and SSG 9.553% with a desirability value of 0.622 which resulted in a weight uniformity (coefficient of variation) of 1.20%, a hardness of 4.55 kg, a friability of 1.68%, and a disintegration time of 124.78 seconds. Verification of the predicted response of the optimum formula showed that the optimization process could predict the response well.